Crime, Gender and Social Control in Early Modern Frankfurt am Main - Kamp, Jeannette (Crime and City in History, 2019)
This book charts the gender differences in crime in early modern Frankfurt. It shows that women's prosecuted crime patterns in Frankfurt were both similar and different to that of other European cities. ; Readership: All interested in the history of crime and gender in early modern Europe, and anyone concerned with the social history of early modern Frankfurt.